2003
DOI: 10.1046/j.1525-1314.2003.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Exhumation of the Main Central Thrust from Lower Crustal Depths, Eastern Bhutan Himalaya

Abstract: Geothermometry and mineral assemblages show an increase of temperature structurally upwards across the Main Central Thrust (MCT); however, peak metamorphic pressures are similar across the boundary, and correspond to depths of 35–45 km. Garnet‐bearing samples from the uppermost Lesser Himalayan sequence (LHS) yield metamorphic conditions of 650–675 °C and 9–13 kbar. Staurolite‐kyanite schists, about 30 m above the MCT, yield P‐T conditions near 650 °C, 8–10 kbar. Kyanite‐bearing migmatites from the Greater Him… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
273
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(289 citation statements)
references
References 48 publications
13
273
2
1
Order By: Relevance
“…In addition to residence time and thermal conditions experienced by the rocks affecting argon loss, they suggested that a ±2 Ma age dispersion would be expected due to diffusive differences caused by grain size variations. MAr ages from eastern Bhutan postdate the age of south-directed shear on the MCT in this region (Stüwe and Foster, 2001;Grujic et al, 2002;Daniel et al, 2003;Kellett et al, 2009;Long et al, 2012). Thus, we interpret the age range of these four MAr samples as the window of permissible exhumation-induced cooling through the modeled closure temperatures of white mica (Ehlers, 2005;Braun, 2003).…”
Section: Thermochronologic Datamentioning
confidence: 70%
See 2 more Smart Citations
“…In addition to residence time and thermal conditions experienced by the rocks affecting argon loss, they suggested that a ±2 Ma age dispersion would be expected due to diffusive differences caused by grain size variations. MAr ages from eastern Bhutan postdate the age of south-directed shear on the MCT in this region (Stüwe and Foster, 2001;Grujic et al, 2002;Daniel et al, 2003;Kellett et al, 2009;Long et al, 2012). Thus, we interpret the age range of these four MAr samples as the window of permissible exhumation-induced cooling through the modeled closure temperatures of white mica (Ehlers, 2005;Braun, 2003).…”
Section: Thermochronologic Datamentioning
confidence: 70%
“…The Greater Himalaya is divided into two structural levels: the lower unit is above the MCT but below the out-of-sequence Kakhtang Thrust (KT), while the higher unit is in the hanging wall of the KT (Grujic et al, 2002). Estimates for the initiation of motion on the MCT range from ∼ 25 to 20 Ma (e.g., Hodges et al, 1996;Daniel et al, 2003;Tobgay et al, 2012), with continued shearing in the Bhutan Himalaya through 18-16 Ma (Grujic et al, 2002;Daniel et al, 2003;Kellett et al, 2009). The age of motion on the KT is notably younger (14-8 Ma; Daniel et al, 2003;Grujic et al, 2002Grujic et al, , 2011Coutand et al, 2014).…”
Section: Tectonostratigraphymentioning
confidence: 99%
See 1 more Smart Citation
“…These 'Grenville'-age orogens surrounded the Indian continent within Gondwanaland and include provinces from east Antarctica (Boger et al 2000;Harley & Kelly, 2007), south-central Africa (Cahen et al 1984) and Sri Lanka/south India (Fitzsimons, 2000a,b). Local potential sources for grains of these ages include magmatic rocks in various tectonic units of Bhutan, Arunachal Pradesh and the Shillong plateau (Daniel et al 2003;Richards et al 2006;Chakungal et al 2010;Yin et al 2010a,b).…”
Section: Detrital Zircon Geochronologymentioning
confidence: 99%
“…In the central Himalaya, most leucogranite emplacement ages are Early-Middle Miocene (~24 to ~12 Ma) [4,9,12,29,31,36,37,69]; but some leucosome yield Oligocene ages [6,23].…”
Section: Timing Of Ductile Deformation Beneath the Ndmentioning
confidence: 99%